Temporal beta diversity and community concordance in freshwater fish and benthic macroinvertebrates on a national scale: Does biodiversity change at the same rate? - Mi-Jung Bae; Eui-Jin Kim (Global Ecology and Conservation)
In this study, we conducted a comprehensive examination of changes in beta diversity over a decade (2009–2019) at 482 sites across five major river basins in South Korea and analyzed the changes in community concordance between freshwater fish and benthic macroinvertebrates. Temporal beta diversity for both fish and macroinvertebrate generally increased across all basins, suggesting continuous changes in their community composition over time. However, the rate and extent of these changes varied substantially among the basins. Moreover, turnover, a measure of species replacement, consistently exceeded nestedness, a measure of species loss or gain. This indicates that species replacement –especially from endemic and anthropogenic disturbance sensitive species to invasive and tolerant species – is the dominant process shaping the observed biodiversity patterns. Furthermore, the degree of similarity between fish and macroinvertebrate communities (i.e., concordance) showed a diverse pattern of changes across the basins, emphasizing that the annual rate of biodiversity change between two communities differs according to the basins. The study's results indicate that species replacements are the dominant force reshaping aquatic communities, with significant implications for ecological resilience and adaptive management. These findings underscore the necessity of continuous biological monitoring and further research incorporating comprehensive environmental data to better understand and mitigate the impacts of environmental changes on biodiversity.